Evaluation of rhinogenic headache in patients submitted to endonasal surgery - Silva, Maria (2013)
Objectives: To investigate if acute sinus infection is the only physiopathological mechanism explaining rhinogenic headaches, as well as to evaluate the efficacy of Turbinectomy, Nasal Turbinates Electrocoagulation, Endoscopic Nasal Surgery and Septoplasty in the improvement of rhinogenic headaches.Study Design: Observational, analytic and retrospective study.Material and Methods: Study sample formed by 44 patients with nasal and sinus pathology whom had undergone surgery between January 1 and March 31, 2012.Results: Chronic sinusitis without acute exacerbation cannot be excluded as being associated with rhinogenic headaches. There were no significant statistical differences between the prevalence of headaches before and after surgery.Conclusion: Other physiopathological mechanisms, different from acute sinus infection, may also explain rhinogenic headaches. Studies with a bigger sample size are necessary to evaluate the efficacy of the cited surgeries in improving headaches.